G611 'Networking across boundaries'-generating best practice for children and young people. The role of local networks in supporting interdisciplinary working. (27th April 2016) - Cardwell, P; Corkin, D; Meehan, M; Carroll, F
Abstract : Aim: Within the RCN children and young people's network, the desire and motivation to support nurses locally in maintaining and developing professional practice within the challenging context of contemporary healthcare, is a key objective. The network aims to deliver learning events which are stimulating, informative and inter-disciplinary in nature, sharing examples of good practice and service development. In support of changing and modernising healthcare the need to work in a collaborative and integrated manner across disciplines and professions is central to the aims of the network (RCN, 2014; DH, 2013). Methods: Local network members recognise the importance of delivering relevant, dynamic and credible learning events, in order to achieve this, it was important to engage across educational and clinical boundaries. Credible and key professionals across disciplines were invited to contribute to these events, which were widely publicised through networks and mailshots to local service providers. As learning events did not form part of a mandatory training portfolio, attendance was as a result of personal desire or relevance to own practice. Results: Programmes of events were supported across disciplines and professions, in delivering diverse, stimulating sessions on service developments, practical workshops and future practice drivers. Each event was well supported and evaluated by delegates, using standardised questionnaires to gather feedback. Evaluative commentary was extremely positive and identified the desire for further conferences and workshops, identifying possible themes for consideration. Additionally, attendees identified activities as meaningful, supportive and enjoyable. In looking forward, members recognise the need to support the future development of the network by inclusive working with HCA and pre-registration nursing students, organising events which recognise their contribution in care delivery to children and young people. Conclusion: Supporting high-quality care to children and young people whilst supporting practice development within current service delivery configurations remains the vision for healthcare across disciplines (RCPCH, 2015). Professional networks such as the RCN children and young people's network plays an important role in bringing together various professionals and disciplines with the view to supporting and developing better working relationships and generating best practice service provision to this patient group and their families.